The Synergistic Effects of Lifestyle Factors and Air Pollution on Pancreatic Dysfunction and Metabolic Disorders: A Literature Review - Aziza Devisafitri (International Journal Labs, 2026)
Pancreatic dysfunction, particularly involving ?-cell failure, is a central factor in the pathogenesis of metabolic disorders. Although intrinsic mechanisms of pancreatic damage have been extensively documented, the combined effects of behavioral and environmental stressors remain an important area of investigation. This literature review synthesized epidemiological and experimental evidence regarding the synergistic effects of lifestyle-related factors and ambient air pollution on pancreatic health. Unhealthy lifestyle behaviors, including obesity, high-fat dietary patterns, physical inactivity, cigarette smoking, and excessive alcohol consumption, contribute to metabolic impairment through glucolipotoxicity, redox imbalance, and systemic inflammation. These factors promote gut dysbiosis and disrupt key insulin signaling pathways. Concurrently, exposure to ambient air pollutants, particularly fine particulate matter (PM?.?), may exacerbate these pathological processes. Particulate matter exposure induces oxidative stress, mitochondrial dysfunction, and endoplasmic reticulum (ER) stress, thereby activating the unfolded protein response (UPR) and NLRP3 inflammasome pathways. The convergence of adverse lifestyle behaviors and chronic air pollution exposure produces synergistic effects that accelerate ?-cell apoptosis and disrupt metabolic homeostasis. Integrated preventive strategies addressing both behavioral modifications and environmental interventions are essential to reduce the increasing burden of type 2 diabetes mellitus in modern industrialized societies.